Pediatric Tibial Osteomyelitis. Issue 5 (July 2016) - Stone, Brad; Street, Matthew; Leigh, Warren; Crawford, Haemish
Abstract : Background: Osteomyelitis shows a strong predilection for the tibia in the pediatric population and is a significant source of complications. The purpose of this article is to retrospectively review a large series of pediatric patients with tibial osteomyelitis. We compare our experience with that in the literature to determine any factors that may aid diagnosis and/or improve treatment outcomes. Methods: A 10-year retrospective review was performed of clinical records of all cases of pediatric tibial osteomyelitis managed at the 2 children's orthopaedic departments in the Auckland region. The Osteomyelitis Database was used to identify all cases between 1997 and 2007, at Starship Children's Hospital, and 1998 and 2008 at Middlemore's Kids First Hospital. Results: One hundred ninety-one patients fulfilled the inclusion criteria, and had a review of clinical notes and relevant investigations. The average duration of symptoms before presentation to hospital was 5.7 days. Less than 40% of patients had a recent episode of trauma. Almost 60% of patients could not bear weight on admission. Over 40% of patients had a temperature above 38°C. Erythrocyte sedimentation rate was elevated in 78% and the C-reactive protein was elevated in 90% of patients. In total, 42% of blood cultures and almost 75% of tissue cultures were positive, with Staphylococcus aureus being the most commonly cultured organism. X-rays, bone scans, and magnetic resonance imaging were all used to aid the diagnosis. About 43% of patients had surgery. Treatment length was an average of 2 weeks 6 days of intravenous antibiotics followed by 3 weeks 2 days of oral treatment. Six postsurgical complications and 46 readmissions were noted: 25 for relapse, with the remainder due to social and antibiotic-associated complications. Conclusions: Although generally diagnosed on presentation, pediatric tibial osteomyelitis can require more sophisticated investigations and prolonged management. Treatment with intravenous and oral antibiotics and surgical debridement where indicated can lead to a good clinical outcome, although complications are often noted. Level of Evidence: Level IV—Prognostic study.